The influence of social factors on gender health - Aboulghar, M; Albertini, D; Allen, J; Bhattacharya, S; Cottingham Terralis C, J; Evers, J; Geraedts, J; Glasier, A; Hunt, K; Hussein, J; La Vecchia, C; Luy, W; et al. (Oxford University Press, 2016)
Male births exceed female births by 5–6%(for a sex ratio at birth of 1.05–1.06) while a women’s life expectancy, on a global scale, is about 6 years longer. Thus within various age groups the male:female ratio changes over time. Until age 50 years men outnumber women; thereafter their numbers show a sharp decline. Consequently at age 80 years, there are many more women than men. An estimated 25% of this male excess mortality is due to biological causes, the rest being explained by behavioural, cultural and environmental factors. For both women and men, the main health risks related to lifestyle are smoking, alcohol, unhealthy diet and physical inactivity. In the year 2010, overweight (BMI: 25–29 kg/m2) and obesity (BMI: .30 kg/m2) were responsible for over 3 million deaths, with similar relative risks in men and women for overweight and obesity. Smoking and alcohol are the major causes of the global gender gap in mortality. For women in some parts of the world however pregnancy is also hazardous. On a global scale, in 2013 about 300 000 deaths were related to pregnancy, with sub-Saharan Africa registering the highest maternal mortality: over 500 maternal deaths per 100 000 births. Additional woman’s health risks arise from gender discrimination, including sex-selective abortion, violence against women and early child marriage. Providers should be aware of the effect that these risks can have on both reproductive and general health.